THE ANALYZING OF AMBIGUITY ON STUDENTS’ WRITING MADE BY STUDENTS IN SMK DHARMA BAKTI MEDAN - Baren, Elya Batu; Ginting, Fiber Yun A.; Tarigan, Karisma E. (Kairos English Language Teaching Journal, 2021)
The aims of this study were to figure out the casual factors of ambiguity found in students writing. The subject of this study was the students of Class XI-TKR of SMK Dharma Bakti Medan. The research design was in the form of descriptive qualitative research. The instrument of collecting data was the studentsâ€™ sheet of English writing text. In conclusion, the most dominant ambiguity in lexical meaning found in writing text by Class XI-TKR of SMK Dharma Bakti Medan was polysemy ambiguity. There were 10 casual factors of why ambiguity found in studentsâ€™ writing text based on the analysis of the structure of sentence in studentsâ€™ English writing. The most reasons were: (1) the students did not give the specific details in their writing, usually they preferred the short writing, (2) there were several vocabularies which could be reasonably interpreted more than one way or reasonably interpretedÂ moreÂ thanÂ oneÂ thing,Â (3)Â theÂ studentsÂ feltÂ confusedÂ toÂ findÂ appropriate vocabularies to express the meaning. As a result, they sometimes left the sentence undone or hanged without a clear idea, due to the lack of vocabularies. The analysis of ambiguity in lexicalÂ meaningÂ thatÂ made byÂ studentsÂ of ClassÂ XI-TKRÂ of SMKÂ DharmaÂ BaktiÂ Medan revealedÂ thatÂ studentsÂ shouldÂ learnÂ semanticÂ asÂ theÂ mainÂ subjectÂ inÂ EnglishÂ writingÂ to understand multiplicity of meanings.